Upaya Meningkatkan Pembelajaran Penididikan Agama Islam Melalui Metode Pemberian Tugas Belajar Pada Siswa Kelas III SDN 02 Timpeh Kecamatan Timpeh Kabupaten Dharmasraya Tahun Pelajaran 2017/2018: Efforts to Improve Learning of Islamic Religious Investigation through the Method of Giving Learning Assignments to Grade III Students of SDN 02 Timpeh, Timpeh District, Dharmasraya Regency, Academic Year 2017/2018 - Lizarni lizarni (Perkumpulan Doktor Indonesia Maju (PDIM), 2022)
Education is a vehicle to improve and develop the quality of human resources. Researchers aim to measure student learning outcomes through PKN learning by using the Multi -Representation Discourse Method (DMR) is a great method to generate many creative ideas that students will not be able to pour just by sitting with a stationery and a sheet of paper. This research is a class action research of qualitative and quantitative approaches. TThe research was conducted in the academic year 2020/2021. The time required for research for 3 months, starting from September-November 2020. Research implementation activities with 2 cycles of action, namely cycle 1 and silkus 2. In each cycle there are activities of planning, implementation, observation and reflection. The results of the study obtained data that the learning outcomes of students (cognitive, affective, and psychomotor) in cycle I has only reached 56% completion with an average value of 64 students while in this cycle II has reached 87.5% completion with an average value of students 84. The conclusion of this activity can be said that the learning results of students of class VI SD Negeri 05 Sitiung Sitiung District in learning PKn using Multi -Representation Discourse Method (DMR) showed a significant improvement. In cycle I the average value obtained by new students reached 60% completion with an average value of 69, while in cycle II showed a fairly high increase with an average value of 82 students with completion reached 86%.